A Perceptual Motor Intervention Improves Play Behavior in Children with Moderate to Severe Cerebral Palsy - Ryalls, Brigette O.; Harbourne, Regina; Kelly-Vance, Lisa; Wickstrom, Jordan; Stergiou, Nick; Kyvelidou, Anastasia (Frontiers in Psychology, 2016)
For children with moderate or severe cerebral palsy (CP), a foundational early goal is independent sitting. Sitting offers additional opportunities for object exploration, play and social engagement. The achievement of sitting coincides with important milestones in other developmental areas, such as social engagement with others, understanding of spatial relationships, and the use of both hands to explore objects. These milestones are essential skills necessary for play behavior. However, little is known about how sitting and play behavior might be affected by a physical therapy intervention in children with moderate or severe CP. Therefore, our overall purpose in this study was to determine if sitting skill could be advanced in children with moderate to severe CP using a perceptual motor intervention, and if play skills would change significantly as sitting advanced. Thirty children between the ages of 18 months and 6 years who were able to hold prop sitting for at least 10 seconds were recruited for this study. Outcome measures were the sitting subsection of the Gross Motor Function Measure (GMFM), and the Play Assessment of Children with Motor Impairment (PACMI) play assessment scale, which is a modified version of the Play in Early Childhood Evaluation System (PIECES). Significant improvements in GMFM sitting scores (p<0.001) and marginally significant improvement in play assessment scores (p=0.067) were found from pre- to post-intervention. Sitting change explained a significant portion of the variance in play change for children over the age of 3 years, who were more severely affected by CP. The results of this study indicate that advances in sitting skill may be a factor in supporting improvements in functional play, along with age and severity of physical impairment.